Structural and piezoelectric coefficients of AlP under pressure - Daoud, Salah; Mezouar, Rabie; Benmakhlouf, Abdelfateh (International Journal of Physical Research, 2018)
The present work aims to investigate the structural parameters and the piezoelectric coefficients of cubic zinc-blende Aluminum phosphide (AlP) under high pressure up to 21 GPa, using plane wave-pseudopotential (PW-PP) approach in the framework of the density functional theory (DFT) and the density functional perturbation theory (DFPT) with the generalized gradient approximation (GGA) for the exchange-correlation functional. The results obtained are analyzed and compared with other data of the literature. The structural parameters and the piezoelectric coefficients calculated here agree well with other data of the literature. We found also that both the direct and converse piezoelectric coefficients increase with increasing pressure up to 21 GPa.Â